Bagongan, Pilkada Serentak dan Demokrasi yang Cedera: Belajar dari Purbalingga - Nurprojo, Indaru Setyo (Political Science Program, Universitas Negeri Semarang, 2016)
This article would like to write about the effects of the simultaneous election policy on the quality of democracy at the local level. In 2015, the election policy applied simultaneously. In practice, the elections simultaneously chosen to emphasize the effectiveness and efficiency of the budget and not for the instruments to the process of deepening democracy. In effect, femonena bagongan happened in the elections Purbalingga. Bagongan has become a form of resistance of the people against the elite political parties and form of movement is unwilling to political parties.